Analysis of the degradation of amorphous silicon‐based modules after 11 years of exposure by means of IEC60891:2021 procedure 3. (29th April 2022) - Piliougine, Michel; Sánchez‐Friera, Paula; Petrone, Giovanni; Sánchez‐Pacheco, Francisco José; Spagnuolo, Giovanni; Sidrach‐de‐Cardona, Mariano
Abstract: The degradation of two amorphous silicon‐based photovoltaic (PV) modules, namely, of single junction amorphous silicon (a‐Si) and of micromorph tandem (a‐Si/ μ ‐Si), after 11 years of exposure in the south of Spain is analyzed. Their I‐V curves were measured outdoors to study the changes of the electrical parameters in the course of three different periods: during the initial days of exposure, during the first year, and in the subsequent 10‐year period. The translation of the curves to an identical set of operating conditions, which enables a meaningful comparison, was done by the different correction procedures described in the standard IEC60891:2021, including the procedure 3, which does not require the knowledge of module parameters, whose values are typically not available. The annual power degradation rates over the entire 11‐year period are 1.12% for the a‐Si module, which is 3.02% for the first year, and 0.98% for the a‐Si/ μ ‐Si, which is 2.29% for the initial year. Abstract : The degradation of a a‐Si/µ‐Si and a a‐Si PV modules is analyzed after 11 years of exposure. The translation of the curves to an identical set of operating conditions was done by IEC60891:2021. The annual power degradation rates are 1.12% for the a‐Si module and 0.98% for the a‐Si/µ‐Si one.